Engineering multi-agent systems : 4th International Workshop, EMAS 2016, Singapore, Singapore, May 9-10, 2016, Revised, selected, and invited papers /: 4th International Workshop, EMAS 2016, Singapore, Singapore, May 9-10, 2016, Revised, selected, and invited papers. (2016) - Unknown
No abstract available